Pendidikan Life Skills Berbasis Budaya Nilai-nilai Islami dalam Pembelajaran - Mawardi, Imam (Nadwa, 2012)
This article explains about life skills education which has role to confirm human function as Allahâs servant and as khalifah in this world. Life skills can help stu-dents to overcome life problems. These skills include the science aspect, mentali-ty, and vocational skills which are related to studentsâ moral development in order to face the problems in their life. The function of life related to Islamic culture is not only as the skill of work but also widely include the skill for doing the duties as an Allahâs servant and khalifah. The development of curriculum based on life skills must be internalized in formal school learning. This idea is based on the view point that education is for the meaning of life and not for look-ing job.